2015 International Conference on Biometrics (ICB) 2015
DOI: 10.1109/icb.2015.7139067
|View full text |Cite
|
Sign up to set email alerts
|

The 1st Competition on Counter Measures to Finger Vein Spoofing Attacks

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…Table 1 and 2 indicates the quantitative performance of the proposed method when compared to 4 different stateof-the-art schemes that was employed in 1st Competition on Counter Measures to Finger Vein Spoofing Attacks [9]. Since the state-of-the-art schemes are based on frame based feature extraction and learning, we have used the training set (see Section 4.1) that comprised of first 50 unique instances with video frames to train the SVM classifier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 and 2 indicates the quantitative performance of the proposed method when compared to 4 different stateof-the-art schemes that was employed in 1st Competition on Counter Measures to Finger Vein Spoofing Attacks [9]. Since the state-of-the-art schemes are based on frame based feature extraction and learning, we have used the training set (see Section 4.1) that comprised of first 50 unique instances with video frames to train the SVM classifier.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we generated the artefacts by printing the real sample using different kinds of printers such as inkjet and laser. The motivation for using the print attack is by because it is very easy to generate, cost effective and already proven to be efficient in a previous study [9]. In order to generate the finger vein artefacts using inkjet printer, we first perform the pre-processing on each of the captured frame of the video by extracting the Region of Extract (ROI) and then rescaling the ROI finger vein to have dimension of 100 × 300 pixels.…”
Section: Real Sample Capturementioning
confidence: 99%
See 1 more Smart Citation
“…In biometric systems, the direct attack or presentation attack is of high interest because of the security evaluation in biometric systems. Finger vein recognition previously had a good spoofing resistance as compared to other biometric modalities, but recent literature has shown that FVR devices are vulnerable to spoof attack [129,130]. In 2007, Matsumoto deceive a system using a synthetic artifact, which was the first attempt to spoof a finger vein image to the best of our knowledge [12].…”
Section: Spoofing Attack (Presentation Attack) In Finger Vein Recognimentioning
confidence: 99%
“…Among past biometrics-oriented challenges, events focusing on fingerprints [31], [32], [33] and facial images [3], [22], [41], [44] have likely been the most visible. Recent years have seen challenges and competitions on other modalities and biometric sub-problems ranging from iris [4], speaker [20], [34], sclera [9], finger-vein [52], [55], or keystroke dynamics [36] recognition to spoof detection [5], [7], [49], liveness detection [19], [35], [53], segmentation [9], [10] and others.…”
Section: Related Workmentioning
confidence: 99%